Healthy Lifestyle and Cardiac Vagal Modulation Over 10 Years: Whitehall II Cohort Study - Jandackova, Vera K; Scholes, Shaun; Britton, Annie; Steptoe, Andrew (Journal of the American Heart Association, 2019)
Background Increased vagal modulation is a mechanism that may partially explain the protective effect of healthy lifestyles. However, it is unclear how healthy lifestyles relate to vagal regulation longitudinally. We prospectively examined associations between a comprehensive measure of 4 important lifestyle factors and vagal modulation, indexed by heart rate variability (HRV) over 10 years. Methods and Results The fifth (1997-1999), seventh (2002-2004), and ninth (2007-2009) phases of the UK Whitehall II cohort were analyzed. Analytical samples ranged from 2059 to 3333 (mean age: 55.7 years). A healthy lifestyle score was derived by giving participants 1 point for each healthy factor: physically active, not smoking, moderate alcohol consumption, and healthy body mass index. Two vagally mediated HRV measures were used: high-frequency HRV and root mean square of successive differences of normal-to-normal R-R intervals. Cross-sectionally, a positively graded association was observed between the healthy lifestyle score and HRV at baseline (Poverall≤0.001). Differences in HRV according to the healthy lifestyle score remained relatively stable over time. Compared with participants who hardly ever adhered to healthy lifestyles, those with consistent healthy lifestyles displayed higher high-frequency HRV (β=0.23; 95% CI, 0.10-0.35; P=0.001) and higher root mean square of successive differences of normal-to-normal R-R intervals (β=0.15; 95% CI, 0.07-0.22; P≤0.001) at follow-up after covariate adjustment. These differences in high-frequency HRV and root mean square of successive differences of normal-to-normal R-R intervals are equivalent to ≈6 to 20 years differences in chronological age. Compared with participants who reduced their healthy lifestyle scores, those with stable scores displayed higher subsequent high-frequency HRV (β=0.24; 95% CI, 0.01-0.48; P=0.046) and higher root mean square of successive differences of normal-to-normal R-R intervals (β=0.15; 95% CI, 0.01-0.29; P=0.042). Conclusions Maintaining healthy lifestyles is positively associated with cardiac vagal functioning, and these beneficial adaptations may be lost if not sustained.
Keywords: autonomic nervous system; dospělí; Heart; hodnocení rizik; chování snižující riziko; Female; lifestyle; Healthy Lifestyle; Adult; ženské pohlaví; pití alkoholu; Alcohol Drinking; London; Protective Factors; Time Factors; srdce; časové faktory; Health Status; lidé; zdravotní stav; nekuřáci; cvičení; Londýn; heart rate variability; Risk Assessment; Habits; srdeční frekvence; Middle Aged; Risk Factors; nervus vagus; Risk Reduction Behavior; prospektivní studie; Male; Cardiovascular Diseases; Aged; zdravý životní styl; Prospective Studies; index tělesné hmotnosti; rizikové faktory; kardiovaskulární nemoci; ochranné faktory; Non-Smokers; Vagus Nerve; lidé středního věku; zvyky; senioři; mužské pohlaví; Body Mass Index; Exercise; Heart Rate; Humans